Nodular histiocytic/mesothelial hyperplasia as consequence of chronic mesothelium irritation by subphrenic abscess. (November 2015) - Cabibi, Daniela; Lo Iacono, Giorgio; Raffaele, Francesco; Dioguardi, Salvatore; Ingrao, Sabrina; Pirrotta, Antonio; Fatica, Federica; Cajozzo, Massimo
Purpose: Pleural nodular histiocytic/mesothelial hyperplasia is a nodular histiocytic/mesothelial proliferation, often delimiting cystic cavities, due to irritation by a pulmonary noxa.Case report results: The patient had right pleural parietal and diaphragmatic thickness, with pleural effusion, without lung alterations. He previously underwent left hemicolectomy and liver resection, due to a diverticulitis and a liver histiocytes-rich abscess. Video-assisted thoracoscopy biopsy showed a double population of reactive mesothelial cells and histiocytes.Conclusion: Nodular histiocytic/mesothelial hyperplasia represents a potential pitfall for pathologists. Immunohistochemistry is crucial for the differential diagnosis with some malignancies. We suggest that in our patient, a chronic mesothelium inflammation happened by transdiaphragmatic involvement as a consequence of the liver abscess. Some pathogenetic mechanisms are hypothesized.